2016
DOI: 10.3835/plantgenome2015.06.0050
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Assembly and Comparison of an Allotetraploid Weed Species, Annual Bluegrass, with its Two Diploid Progenitor Species, Poa supina Schrad and Poa infirma Kunth

Abstract: Annual bluegrass (Poa annua L.) is one of the most widespread weed species in this world. As a young allotetraploid, P. annua has occupied diverse environments from Antarctic area to subtropical regions. To unveil the evolutionary mystery behind P. annua's wide distribution, extensive adaptability and phenotypic plasticity needs collaboration from multiple research scopes from ecology and plant physiology to population genetics and molecular biology. However, the lack of omic data and reference has greatly ham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Interestingly, results here show that mutations arose exclusively in P. supina homoeologous alleles in R, whereas P. infirma homoeologous alleles remained unchanged even upon selection pressure of glyphosate. These findings corroborate a report by Chen et al, 36 who observed that the nucleotide percentage differences from nuclear genes in the P. supina sub-genome are considerably higher than in the P. infirma sub-genome. Cross et al 37 also found that target-site mechanisms are involved in glyphosate resistance in a P. annua biotype from South Carolina.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, results here show that mutations arose exclusively in P. supina homoeologous alleles in R, whereas P. infirma homoeologous alleles remained unchanged even upon selection pressure of glyphosate. These findings corroborate a report by Chen et al, 36 who observed that the nucleotide percentage differences from nuclear genes in the P. supina sub-genome are considerably higher than in the P. infirma sub-genome. Cross et al 37 also found that target-site mechanisms are involved in glyphosate resistance in a P. annua biotype from South Carolina.…”
Section: Discussionsupporting
confidence: 92%
“…S exclusively exhibited the wild-type EPSPS at coding positions 102 and 106, with P. supina and P. infirma EPSPS homoeologous alleles both represented based on sequence similarity with previously published sequencing data. 36 Conversely, line R exhibited a SNP at coding position 106 of the P. supina EPSPS homoeolog, resulting in a leucine substituting a proline, whereas the P. infirma EPSPS homoeologs had only the wild-type codon. A ratio of 9 : 1 P. supina EPSPS to P. infirma EPSPS alleles in R was observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The assembly and homology search statistics are all congruent with previous transcriptome studies in Poaceae . The observed N50 for A. spica-venti are similar to the values from Lolium spp de novo transcriptome (771 bp; [ 23 ]), L. rigidum (1,150: [ 22 ]), Leymus chinensis (813: [ 33 ]) and Phragmites australis (1,187 bp; [ 34 ]), but are lower when compared to Zea mays (1,612 bp :[ 30 ]), and Arundo donax (2,229 bp ; [ 35 ]), Poa annua (1,602 bp: [ 25 ]), L. perenne (1,500 bp: [ 36 ]), and Eleusine indica (2,095 bp: [ 24 ]). The number of transcript after redundancy reduction is slightly lower than the number found after filtering in Lolium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome data have been used in different weed species to study the origin of polyploidy events [ 9 , 10 ], to understand genetics and biology of weeds [ 11 14 ], and to investigate herbicide resistance [ 15 – 22 ]. The majority of transcriptomic studies have focused on dictoyledonous weed species and only four grass weeds have been investigated at the transcriptomic level: Lolium rigidum [ 22 , 23 ], Eleusine indica [ 24 ], Poa annua [ 15 , 25 ], and Echinocloa cruss-galli [ 16 ]. The investigation into evolutionary and molecular processes in these weeds is therefore facilitated by the availability of molecular data.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-Seq reads were downloaded from NCBI (Additional File 8) were downloaded from NCBI and converted to fastq format with fastq-dump v2. condensed into a set of unigenes using cd-hit v4.7 [77] with default flags.…”
Section: Transcriptome Assembly For Phylogenomicsmentioning
confidence: 99%